Male and Female Characteristics of Facial Soft Tissue Thickness in Different Orthodontic Malocclusions Evaluated by Cephalometric Radiography - krishna veni, Sampath; krishna, Polisetty Siva; vamsi, Kogila Jashva (Journal of Neonatal Surgery, 2025)
Background: This study was conducted to assess the Male and Female Characteristics of Facial Soft Tissue Thickness in Different Orthodontic Malocclusions Evaluated by Cephalometric Radiography. Material and methods: This research involved the assessment and analysis of lateral cephalograms derived from cephalometric radiography to determine facial soft tissue thickness (FSTT) in a cohort of 100 adult orthodontic patients, comprising 60 females and 40 males. The lateral cephalograms were obtained as part of standard diagnostic procedures for the patients under evaluation. Individuals were excluded from the study if they had experienced trauma, had craniofacial anomalies, cleft lip and palate, or had undergone previous orthodontic, prosthetic, or orthognathic surgical interventions. All participants included in the study received a comprehensive clinical evaluation, which encompassed an analysis of their dental and skeletal characteristics, as well as their soft tissue profiles as observed in the cephalometric radiography. The statistical analysis was conducted using a database where the data were organized. Results: In this study, there were 40 males and 60 females. The findings showed that male patients had a significantly greater facial soft tissue thickness in A-SN, PR-SLS and J-LS areas as compared to females. Conclusion: From the findings of this study, it can be concluded that patients had a significantly greater facial soft tissue thickness in A-SN, PR-SLS and J-LS areas as compared to females.